2000
DOI: 10.1089/jop.2000.16.407
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Interleukin-1-Induced Uveitis and Corneal Fibroblast Proliferation by Interleukin-1 Blockers

Abstract: Interleukin-1 (IL-1) is known to trigger induction of inducible nitric oxide synthase (iNOS) to persistently mass produce nitric oxide (NO) to induce various diseases such as cancer, inflammation, Alzheimer's disease and eye diseases, including uveitis, retinopathy, age-related macular degeneration, glaucoma and myopia. Therefore, IL-1 blockers could become an important class of drugs to fight numerous diseases. Among the many compounds studied so far, 1-methyl hydrazino analogs are among the most promising ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…5 Inflammatory mediators involved in ocular disease have recently become of interest as potential therapeutic targets for the inhibition of inflammation in the eye, including nitric oxide synthase, tumor necrosis factor (TNF), interleukin-1 (IL-1), and cyclooxygenase-2 (COX-2)–generated prostanoids. 7,12 Prostanoids are the products of arachadonic acid (AA) metabolism by the COX enzymes. 5,6 Two isoforms of COX have been identified, COX-1 and COX-2.…”
mentioning
confidence: 99%
“…5 Inflammatory mediators involved in ocular disease have recently become of interest as potential therapeutic targets for the inhibition of inflammation in the eye, including nitric oxide synthase, tumor necrosis factor (TNF), interleukin-1 (IL-1), and cyclooxygenase-2 (COX-2)–generated prostanoids. 7,12 Prostanoids are the products of arachadonic acid (AA) metabolism by the COX enzymes. 5,6 Two isoforms of COX have been identified, COX-1 and COX-2.…”
mentioning
confidence: 99%
“…Several studies have also shown that IL-1 is a potent stimulator of fibroblast proliferation (5,(7)(8)(9)26,27), and Inokuchi et al (28) demonstrated that IL-1α stimulates cell proliferation through Ca 2+ /calmodulindependent pathway in NIM 1 cells, a human thyroid cell line established from a patient with thyroid papillary adenocarcinoma. The findings of recent papers that the IL-1 blockers, CK-119 and CK-122 (29) and 1-methyl hydrazine analogs (30,31) inhibit the cell proliferation in human lung fibroblasts and fibroblast-like cells, respectively, also suggest that IL-1 enhances cell growth in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting inflammatory cytokines like interleukin-1 (IL-1) and tumor necrosis factor-α, RLRL may lower their amounts [ 57 ]. Additionally, severe myopia may substantially raise IL-1 and IL-6 levels, which may be related to the myopic control mechanism [ 58 , 59 ]. According to a generally accepted theory, bright light causes the retina to produce and release more dopamine [ 60 ].…”
Section: Discussionmentioning
confidence: 99%